2001
DOI: 10.1111/j.1572-0241.2001.03384.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive multiple myeloma presenting as mesenteric panniculitis

Abstract: Mesenteric panniculitis is a rare disease of the bowel mesentery, characterized by tumor-like infiltration by chronic inflammatory cells, fat necrosis, and fibrosis. Reported cases cited clinical presentation ranging from abdominal pain to fever of unknown origin, the majority of which were idiopathic and associated with a benign prognosis. We report the case of a 43-yr-old male who presented with malaise, weight loss, microcytic anemia, and a high erythrocyte sedimentation rate. Radiographic and histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 11 publications
1
18
0
6
Order By: Relevance
“…A variety of possible causative factors have been proposed, such as autoimmune disorders, ischemia and prior abdominal surgery. In addition, it has also been suggested that mesenteric panniculitis might represent a paraneoplastic response [1,8,9]. This latter possible association with a concomitant malignancy has recently been highlighted in a study by Daskalogiannaki [1], reporting the presence of a coexisting abdominal or distal malignancy in 69% of patients with CT features of mesenteric panniculitis.…”
Section: Pathogenesismentioning
confidence: 96%
“…A variety of possible causative factors have been proposed, such as autoimmune disorders, ischemia and prior abdominal surgery. In addition, it has also been suggested that mesenteric panniculitis might represent a paraneoplastic response [1,8,9]. This latter possible association with a concomitant malignancy has recently been highlighted in a study by Daskalogiannaki [1], reporting the presence of a coexisting abdominal or distal malignancy in 69% of patients with CT features of mesenteric panniculitis.…”
Section: Pathogenesismentioning
confidence: 96%
“…Others may also be affected including the gallbladder, adrenals, bladder, mesentery, and reproductive organs. (4,6,7). When affecting the liver, myeloma is typically a diffusely infiltrative process, leading to intrahepatic cholestasis and jaundice.…”
Section: Discussionmentioning
confidence: 98%
“…11) or permeative and infiltrative tumor growth. The extraosseous myeloma present as mesenteric panniculitis (9). Under these conditions, abdominal CT scans showed mesenteric thickening and inhomogeneous areas of fat interspersed with soft-tissue attenuation.…”
Section: Mesentery and Peritoneummentioning
confidence: 99%